Design of energy efficient optical networks with software enabled integrated control plane. Issue 1 (1st January 2015) - Wang, Jiayuan; Yan, Ying; Dittmann, Lars
Abstract : The growing energy consumption has posed new challenges for the future development of networks. Some earlier work has proposed solutions to improve energy consumption based on the existing control plane, for example, node/links sleeping. This study presents a new possibility to reduce network energy consumption by proposing a new integrated control plane structure utilising Software Defined Networking technologies. The integrated control plane increases the efficiencies of exchanging control information across different network domains, while introducing new possibilities to the routing methods and the control over quality of service (QoS). The structure is defined as an overlay generalised multi‐protocol label switching (GMPLS) control model. With the defined structure, the integrated control plane is able to gather information from different domains (i.e. optical core network and the access networks), and enable energy efficiency networking over a wider area. In the case presented, the integrated control plane collects the network energy related information and the QoS requirements of different types of traffic. This information is used to define the specific group of traffic's (flow's) routing behaviours. With the flexibility of the routing structure, results show that the energy efficiency of the network can be improved without compromising the QoS for delay/blocking sensitive services.